(untitled) (Fiep Bulletin - online, 2016)
Increased body fat and thus overweight and obesity is causes mainly by changes in life style, such as physical inactivity and increased food intake. In elderly Instead muscles there is aproportional increase in fat, especially in the pelvic girdleand this tends to be centralized, making it more visceral, bringing numerous diseases such as metabolic syndrome and thus heart disease. This study aimed to determine the prevalence of obesityfrom the CPandthe risk factors for CVDin the elderly. The studyiscross-sectional,including 85elderlybetween 60 and93 years, residentsof Vitoria-ES. Neck circumference, waist,hip,body mass and heightwas used. The study populationisobeseasthebody adiposityindex, neck circumferenceandwaist. The dataobtained demonstrated that CPas well asthe CCandIAC may beused as amarker foranthropometricestimatecardiovascular risk.Individuals withincreased CP may contain higher proportionsof hypertension, diabetes, dyslipidemia, obesity andchangesin the indicatorsstudied.